Screening for Fabry disease in patients with left ventricular noncompaction - Olga Azevedo (Revista Portuguesa de Cardiologia (English Edition), 2019)
Introduction and Aim: It is unclear whether left ventricular noncompaction (LVNC) is a distinct cardiomyopathy or a morphologic manifestation of different cardiomyopathies. We previously reported a case of LVNC in a Fabry disease (FD) patient, but it remains to be clarified whether LVNC is a cardiac manifestation of FD, a coincidental finding or an overdiagnosis, which has major therapeutic implications. This study aims to determine the prevalence of FD among patients with LVNC. Methods: We performed a retrospective study including all patients diagnosed with LVNC in eight hospital centers. Diagnosis of LVNC was based on at least one echocardiographic or cardiac magnetic resonance criterion. FD screening was performed by combined enzyme and genetic testing. Results: The study included 78 patients diagnosed with LVNC based on the Jenni (84.6%), Stöllberger (46.2%), Chin (21.8%), Petersen (83.8%) and Jacquier (16.2%) criteria. Left ventricular systolic dysfunction was present in 48.7%. Heart failure was found in 60.3%, ventricular dysrhythmias in 21.6% and embolic events in 11.5%. FD screening found no additional cases among patients with LVNC, besides the previously described case. Conclusion: No additional FD cases were found among patients with LVNC, which argues against the hypothesis that LVNC is a cardiac manifestation of FD. Resumo: Introdução e objetivo: Não está esclarecido se a não compactação do ventrículo esquerdo (NCVE) é uma miocardiopatia distinta ou uma manifestação morfológica de várias miocardiopatias. Nós reportamos previamente um caso de NCVE num doente com doença de Fabry (DF), mas permanece por esclarecer se a NCVE é uma manifestação cardíaca de DF, um achado coincidente ou um sobrediagnóstico, o que tem importantes implicações terapêuticas. Este estudo pretende determinar a prevalência de DF em doentes com NCVE. Métodos: Estudo retrospetivo incluindo todos os doentes diagnosticados com NCVE em oito centros hospitalares. O diagnóstico de NCVE foi baseado em pelo menos um dos critérios de ecocardiografia ou ressonância cardíaca. O rastreio de DF foi realizado por teste enzimático e genético. Resultados: O estudo incluiu 78 doentes diagnosticados com NCVE com base nos critérios de Jenni (84,6%), Stöllberger (46,2%), Chin (21,8%), Petersen (83,8%) e Jacquier (16,2%). A disfunção sistólica do VE estava presente em 48,7%. A insuficiência cardíaca foi encontrada em 60,3%, as disritmias ventriculares em 21,6% e os eventos embólicos em 11,5%. O rastreio de DF não encontrou casos adicionais nos doentes com NCVE, para além do caso previamente descrito. Conclusão: Não foram encontrados casos adicionais de DF nos doentes com NCVE, o que argumenta contra a hipótese de a NCVE ser uma manifestação cardíaca de DF. Keywords: Fabry disease, Noncompaction, Hypertrabeculation, Cardiomyopathy, Screening, Palavras-chave: Doença de Fabry, Não compactação, Hipertrabeculação, Cardiomiopatia, Rastreio